Discrimination Against Sexual Minorities in Education and Housing : Evidence from Two Field Experiments in Serbia - Koehler, Dominik; Harley, Georgia; Menzies, Nicholas (World Bank, Washington, DC, 2018)
Discrimination against lesbian, gay, bisexual, transgender, and intersex (LGBTI) people is widespread, and LGBTI exclusion from economic markets, vital services, and political spaces is entrenched. This is not just an individual problem; it is a development challenge; not only because discrimination is inherently unjust, but also because “there are substantial costs -- social, political, and economic -- to not addressing the exclusion of entire groups of people.” Understanding the barriers LGBTI people face in accessing markets, services, and spaces is important for designing more inclusive policies and programs. This study documents, for the first time, discrimination against LGBTI people in access to education and housing in Serbia, using evidence from field experiments. In Serbia, "feminine boys," widely perceived as being gay, were at least three times more likely to be refused enrollment in primary schools (15 percent) compared to boys not perceived to be feminine (5 percent). Eighteen percent of same-sex couples were refused apartment rentals by private landlords, while no heterosexual couples were. The research contributes to the growing body of evidence on the economic dimensions of LGBTI discrimination.